Outcomes of domestic violence screening at an acute London trust: are there missed opportunities for intervention?. Issue 1 (4th January 2016) - Warren-Gash, Charlotte; Bartley, Angela; Bayly, Jude; Dutey-Magni, Peter; Edwards, Sarah; Madge, Sara; Miller, Charlotte; Nicholas, Rachel; Radhakrishnan, Sheila; Sathia, Leena; Swarbrick, Helen; Blaikie, Dee; et al.
Abstract : Objectives: Domestic violence screening is advocated in some healthcare settings. Evidence that it increases referral to support agencies or improves health outcomes is limited. This study aimed to (1) investigate the proportion of hospital patients reporting domestic violence, (2) describe characteristics and previous hospital attendances of affected patients and (3) assess referrals to an in-house domestic violence advisor from Camden Safety Net. Design: A series of observational studies. Setting: Three outpatient clinics at the Royal Free London NHS Foundation Trust. Participants: 10 158 patients screened for domestic violence in community gynaecology, genitourinary medicine (GUM) and HIV medicine clinics between 1 October 2013 and 30 June 2014. Also 2253 Camden Safety Net referrals over the same period. Main outcome measures: (1) Percentage reporting domestic violence by age group gender, ethnicity and clinic. (2) Rates of hospital attendances in the past 3 years for those screening positive and negative. (3) Characteristics, uptake and risk assessment results for hospital in-house domestic violence referrals compared with Camden Safety Net referrals from other sources. Results: Of the 10 158 patients screened, 57.4% were female with a median age of 30 years. Overall, 7.1% reported ever-experiencing domestic violence, ranging from 5.7% in GUM to 29.4% in HIV services. People screening positive for domestic violence had higher rates of previous emergency department attendances (rate ratio (RR) 1.63, 95% CI 1.09 to 2.48), emergency inpatient admissions (RR 2.27, 95% CI 1.37 to 3.84) and day-case admissions (RR 2.03, 95% CI 1.23 to 3.43) than those screening negative. The 77 hospital referrals to the hospital-based domestic violence advisor during the study period were more likely to be taken up and to be classified as high risk than referrals from elsewhere. Conclusions: Selective screening for domestic violence in high-risk hospital clinic populations has the potential to identify affected patients and promote good uptake of referrals for in-house domestic violence support.